Pengaruh Media Articulate Storyline terhadap Hasil Belajar Siswa pada Materi IPS Kelas V SDN Menanggal 601 Surabaya - Purba, Novia Kristina; Sulistyawati, Ida; Satyaningsih, Rarasaning (EDUPEDIA Publisher, 2023)
The purpose of this study was to find out how the influence of Articulate Storyline as a learning medium on student learning outcomes. This study uses a quantitative approach and uses a quasi-experimental research design with a posttest only control group design. Simple random sampling method, which is a probability sampling technique, was used to collect research subjects from class V SDN Menanggal 601 Surabaya, which consisted of 73 students. Data collection was carried out through a posttest assessment at the end of the lesson. In addition, various methods of data analysis were used in this study including the normality test (Kormogolov-Smirnov test), homogeneity test (Levene test), and homogeneity test (Independent Sample T-Test). All of these techniques were used using the SPSS version 22 program. The results of the Independent Sample T-Test showed that the t value was 24.108 with a significance of 0.000, which indicated that the t value was significant (p = 0.000 <0.005). Ho is rejected and Ha is accepted if the significance value is t <0.05. Thus it can be concluded that the Articulate Storyline learning media influences student learning outcomes on social studies material in class V SDN Menanggal 601 Surabaya.